Cosmic Biology How Life Could Evolve on Other Worlds - Irwin, Louis Neal.; Schulze-Makuch, Dirk.; SpringerLink (Online service) (New York, NY : Praxis : Imprint: Praxis, 2011)
It is very unlikely that little green humanoids are living on Mars. But what are the possible life forms that might exist in our Solar System and how might they have evolved? This uniquely authoritative and imaginative book on the possibilties for alien life addresses the intrinsic interest that we have about life on other worlds - reinforcing some of our assumptions and reshaping others. It introduces new possibilties that will enlarge our understanding of the issue overall, in particular the enormous range of environments and planetary conditions within which life might evolve. Cosmic Biology -discusses a broad range of possible environments where alien life might have evolved; -explains why carbon-based, water-borne life is more likely that its alternatives, but is not the only possiblity; -applies the principles of planetary science and modern biology to evolutionary scenarios on other worlds; -looks at the future fates of living systems, including those on Earth.
Preface -- List of Illustrations -- Chapter 1: Rare Earths and Life Unseen -- Chapter 2: Life, Chemistry, Action! -- Chapter 3: Life's Fundamentals -- Chapter 4: Fire and Water -- Chapter 5: Frozen Desert -- Chapter 6: Hell Fire and Brimstone -- Chapter 7: Suspended Animation -- Chapter 8: Deep and Dark -- Chapter 9: Fire and Ice -- Chapter 10: Petrolakes -- Chapter 11: Exotic Cocktails -- Chapter 12: Biocomplexity in the Cosmos -- Chapter13: Anticipating the Future -- Glossary -- Index.
Keywords: Physics; Bioorganic chemistry; Astrophysics; Astrobiology; Astronomy; Physics; Astrobiology; Popular Science in Astronomy; Extraterrestrial Physics, Space Sciences; Animal Systematics/Taxonomy/Biogeography.; Bioorganic Chemistry